Analisis Watak Tokoh dalam Novel Sebening Senja Karya Nawank Wulan Kajian Psikologi - Dwi Sistiana (Universitas PGRI Palembang, 2016)
Literary work born caused basic human impulse to express a feeling of the contents of his heart , and his mind , put the interests of human problem and humanity , and the existence of attention to the world the reality of that lasted all day and all the days of . The study psychology, researchers used tipe-tipe nature of the figures in terms of interpersonal needs according to william c. Schutz namely: in terms of ketermasukan; terms of power, both keafektifan. Problems in research is: (1) how psychological analysis in a novel sebening senja work nawank wulan theory personality william c .Shutz . Methods used in research is a qualitative descriptive with psychological approach to the nature of the novel can be classified properly. Based on the research done it is known that psychological .In a novel sebening senja it has found psychological which includes type or inclusion , type power or control and type keafektifan or affection. Keysword: novel, psychological, humanity